The impact of an otolaryngology inpatient consult documentation improvement program - Farrukh R. Virani; Peter C. Wickwire; Debbie A. Aizenberg (Laryngoscope Investigative Otolaryngology, 2022)
Abstract Objective In an era of limited medical training funds and challenges for teaching centers to maintain their academic mission, the importance of accurate documentation to ensure commensurate coding and billing for services is critical. We sought to develop a practical program that would teach residents documentation skills with the goal of more accurately capturing the work being done in a tertiary care academic medical center. Methods A case–control study was performed. Otolaryngology inpatient and Emergency Department consultation notes at a single tertiary medical center were reviewed and knowledge gaps and shortcomings in documentation identified. Three short educational sessions were provided on documentation skills. During the same timeframe, templates in the electronic medical record were standardized to help maintain thoroughness of documentation within the consultation note. Results A total of 1476 consultations performed by the Otolaryngology department during a 9‐month period in FY17/18 (preintervention) were compared to a total of 1622 consultations performed during the same 9‐month period in FY19/20 (postintervention). The percent of billable consultations increased from 42.4% to 50.9% (p < .001). Similarly, the percentage of consultations coding at a higher level of complexity rose from 51.6% to 59.5% (p = .002). This improvement led to an increase in consultation charges of more than $130,000. Conclusion This study demonstrates that a simple documentation and coding curriculum and workflow interventions can lead to more thorough and improved consult documentation as evidenced by a significant increase in the percentage and complexity of billable Otolaryngology consultations at a tertiary academic center. Level of Evidence 4.